Design and implementation of a prototype web-accessible online catalog for the U.P. Main Library using an existing CDS/ISIS database - Saguban, Angie A.; Uy, Mark Benedict O.; Angeles, Chito N. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2000)
This study aimed to determine the University of the Philippines (UP) Diliman Main Library on-line public access catalog (OPAC) users' profile, user evaluation of the existing OPAC, OPAC features, users' and library staff needs/desires, and fields/features permissible on a web-accessible OPAC. Based on these information, the researchers designed and implemented a prototype accessible OPAC that caters to the needs of the Main Library using the existing Micro-CDS/ISIS software and PERL programming language.
The study employed the survey method with questionnaires personally distributed to a randomly selected number of Main Library staff (from a list of staff performing OPAC-related tasks) and to a systematically sampled Main Library OPAC users. The gathered data were then subjected to statistical analysis using either Chi-square goodness-of-fit test statistic or Binomial test.
The results of the survey show that 61 percent of the users sampled have no experience or are novices in computer-related tasks. The study also found that 61 percent of the OPAC users had never used the Internet. The results also indicated that majority of the OPAC users used the UP Main Library's OPAC weekly on average and that 44 percent of the users have learned to use the OPAC by themselves, 23 percent learned by reading posted instructions and 22 percent learned through the help of friends and classmates. The respondents, in general, were not able to use other OPAC software.
Based on the data gathered, it was learned that the users slightly agree that the current OPAC is easy to use, is flexible and simple, provides uniformity and consistency in the data format, can be learned by one's self, and gives fast and speedy information they demand. All named features such as ease of use, speedy access to information, accuracy of data, availability of navigation facilities, remote access, etc. were found to be highly needed and desired OPAC features. OPAC users also believe that the logical AND search operators as well as specific and all field searching are highly needed. In terms of web-accessibility, OPAC users would not access the Main Library OPAC at Internet cafes whether inside or outside the campus, or at home or at friends' and relatives dial-up systems. Twenty-eight percent (28) would use it weekly at the Main Library and 23 percent would use it weekly at University-based facilities. Majority of the respondents prefer to have the Main Library's OPAC accessible from the web 24 hours a day from Mondays-Saturdays.
The study also found that the library staff see the accessibility of the library database via the web as desirable and allowable. An alternative search interface for users is also considered desirable and allowable. Author, title, location and publication date can be made available to in-house (within the Main Library), Dilnet and dial-up connections. The results further indicated that it would be desirable and allowable by the staff to have other features such as library news/update and on-line help to be made available on the web-accessible OPAC.
The study also discussed the design of the prototype web-accessible OPAC, which consists of the user interface (HTML), the PERL program and the ISO file generated by the Main Library CDS/ISIS database. For security purposes, the HTML, PERL and CGI programming codes were not attached to the final documentation of the study but can be viewed and studied by any interested party with a written permission from the researchers and the head of the technical division of the Main Library.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: CDS/ISIS (Information retrieval system).; Online catalogs -- Philippines -- Quezon City; University of the Philippines Diliman Main Library; Web sites